LITERASI TUMBUHAN LANGKA MAHASISWA PENDIDIKAN BIOLOGI SEBAGAI HASIL TUGAS MINI RISET PERKULIAHAN BIOLOGI TUMBUHAN - Sariwulan Diana; Ana Ratna Wulan; Sri Anggraeni (EDUSAINS, 2019)
RARE PLANT LITERACY FOR BIOLOGICAL EDUCATION STUDENTS AS A RESULT OF THE TASK OF MINI RESEARCH AbstractIndonesia is known as one of the mega biodiversity countries, but ironically biodiversity in Indonesia has actually decreased, so that there are around 240 species of plants already included in the list of endangered plants. Therefore a movement is needed to educate the academic community, in this case Biology Education students through lecture assignments about endangered plant literacy.  Thus the problem in this study is how the literacy of endangered plants of Biology Education students as a result of mini research in plant biology lectures. This research is a descriptive research. The research instruments included a mini research assessment sheet, which included aspects of the accuracy of determining plant species which included endangered categories, descriptions of morphology, classification and benefits of these plants. Biology Education students are assigned to survey, inventory and observe endangered plants in West Java. Overall endangered plant literacy of Biology Education students is good, but the aspect that is still lacking is in determining plant species in endangered categories. One of the plants found in Sukabumi area is Cynometra cauliflora including vulnerable plants. Need to develop assignments and assessments to assess endangered plant literacy of students to be more comprehensive. AbstrakIndonesia dikenal sebagai salah satu negara mega biodiversitas tetapi ironisnya  keanekaragaman hayati di Indonesia justeru  mengalami penurunan, sehingga  ada sekitar  240 jenis tumbuhan sudah masuk dalam daftar tumbuhan langka. Oleh karena itu perlu dilakukan suatu gerakan untuk mengedukasi masyarakat akademis, dalam hal ini mahasiswa Pendidikan Biologi melalui tugas perkuliahan tentang literasi tumbuhan langka.  Dengan demikian masalah yang diangkat pada penelitian ini adalah bagaimana literasi tumbuhan langka mahasiswa Pendidikan Biologi  sebagai hasil tugas mini riset perkuliahan biologi tumbuhan. Penelitian ini merupakan penelitian deskriptif. Instrumen penelitian meliputi lembar penilaian  mini riset, yang meliputi aspek ketepatan penentuan spesies tumbuhan yang termasuk kategori langka,  deskripsi morfologi, klasifikasi dan  manfaat tumbuhan tersebut. Mahasiswa  Pendidikan Biologi  ditugaskan untuk mensurvey, menginventarisasi dan mengobservasi tumbuhan langka yang berada di daerah Jawa Barat. Secara keseluruhan literasi tumbuhan langka mahasiswa Pendidikan Biologi termasuk baik, tetapi aspek yang masih kurang sekali adalah pada penentuan spesies tumbuhan dalam kategori langka. Salah satu tumbuhan yang ditemukan di daerah Sukabumi adalah  Cynometra cauliflora termasuk tumbuhan berstatus rawan. Perlu pengembangan penugasan dan asesmennya  untuk menilai literasi tumbuhan langka mahasiswa agar  lebih komprehensif.